Modelling groundwater pollutant transfer mineral micropollutants in a multi-layered aquifer in Burkina Faso (West African Sahel) - Moussa Diagne Faye; Vini Yves Bernadin Loyara; Angelbert Chabi Biaou; Roland Yonaba; Mahamadou Koita; Hamma Yacouba (Heliyon, 2024)
In Burkina Faso, human activities around water points in rural areas affect groundwater resources, which become unfit for consumption. Nearly 33.5% of boreholes are subject to point source pollution. The assessment of the evolution of such pollution should be monitored to assess groundwater quality. In addition, withdrawals for irrigation alone are estimated at 85%, i.e. 46% of the water demand, heightening the deterioration in quality while creating depression zones further leading to an increase in recharge. It is therefore critical to understand the evolution and fate of the transfer of pollutants in such environments. In this study, we aimed to model the transfer of pollutant and predict the future state of pollution using the MT3D-USGS Groundwater Solute Transport Simulator code through the Groundwater Modelling Software (GMS) over the period 2012–2062 (50 years). A mathematical model is further developed through inferential statistics and used as a surrogate model for comparison. The results showed that deterioration in water quality was more attributable to withdrawals, especially for Cyanide (Cn) and Arsenic (As). A rather slow degradation is reported for Lead (Pb), which extends over 22 km, and Fluoride (F), which extends from 4 to 10 km due to localized recharge. A faster degradation for Cn over a distance of 2–16 km and as from 3 to 11 km is also observed because of the geological setting of the subsoil. These results might assist decision-makers for the quantitative and qualitative management of groundwater resources, and the management of the basement aquifer in the area through the establishment of protection zones.